Consumption response to minimum wages: Evidence from Chinese households - Ernest Dautović; Harald Hau; Yi Huang (European Central Bank (ECB), 2019)
The paper evaluates the impact of the Chinese minimum wage policy on consumption of low-wage households for the period 2002-2009. Using a representative household panel, we find that the consumption response to minimum wage income shock is increasing in the minimum wage share of household income and that poorer households fully consume their additional income. The large marginal propensity to consume is driven by households with at least one child, while childless poor households save two thirds of a minimum wage hike. The expenditure increase is concentrated in health care and education with potentially long-lasting benefits to household welfare.
Keywords: E24; J38; C26; 330; Minimum wages; labor income; transfer income; household consumption